2000
DOI: 10.1046/j.1365-2362.2000.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

The polysaccharide fucoidan inhibits microvascular thrombus formation independently from P‐ and l‐selectin function in vivo

Abstract: Taken together, our novel findings suggest that fucoidan effectively prevents microvascular thrombus formation induced by endothelial damage in arterioles and venules in vivo. This protective effect of fucoidan is not attributable to inhibition of P- and L-selectin function but may instead be related to the anticoagulative capacity of fucoidan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 35 publications
6
40
0
1
Order By: Relevance
“…Fucoidan interferes with selectins which could inhibit binding of platelets and leukocytes to endothelial cells and thus prevent thrombosis. However, as previously reported by Thorlacius et al [20] with a higher molecular weight fucoidan, the antithrombotic effect of LMWF was not mediated by inhibition of P-selectin, as we observed no significant difference in P-selectin expression among the 3 groups of animals [20]. Moreover, we ruled out a major contribution of leukocytes in our model, as leukocytes were detected in very small numbers in the media of the arteries in the 3 groups.…”
Section: Discussionsupporting
confidence: 69%
“…Fucoidan interferes with selectins which could inhibit binding of platelets and leukocytes to endothelial cells and thus prevent thrombosis. However, as previously reported by Thorlacius et al [20] with a higher molecular weight fucoidan, the antithrombotic effect of LMWF was not mediated by inhibition of P-selectin, as we observed no significant difference in P-selectin expression among the 3 groups of animals [20]. Moreover, we ruled out a major contribution of leukocytes in our model, as leukocytes were detected in very small numbers in the media of the arteries in the 3 groups.…”
Section: Discussionsupporting
confidence: 69%
“…The effects of fucoidan on survival rate and spleen function were prophylactic, rather than therapeutic, suggesting that fucoidan requires time to protect target cells against the harmful effects of LPS. Based on previous studies, fucoidan blocks selectin-dependent leukocyte adhesion/rolling [13,14] and inhibit microvascular thrombus formation [15]. It is thus suggested that fucoidan may affect blood circulation dysfunction by LPS in mice.…”
Section: Discussionmentioning
confidence: 93%
“…For the study of vascular thrombus formation, we used the opened cremaster muscle preparation, as described originally by Baez [16] and applied as a model of microvascular thrombus formation in previous studies [17][18][19][20]. After the preparation of the cremaster muscle, the animals were allowed to recover from surgery for 15 min before induction of thrombus formation.…”
Section: Mouse Cremaster Muscle Preparationmentioning
confidence: 99%